Novel poly(amide-hydrazide)s and copoly(amide-hydrazide)s from Bis-(4-aminobenzyl) hydrazide and aromatic diacid chlorides: synthesis and characterization - Medhi, M.; Patil, A. S.; Halhalli, Mahadeo R.; Choubey, A.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Applied Polymer Science, 2010)
A new aromatic diamine, viz., bis-(4-aminobenzyl) hydrazide (BABH), which contains preformed hydrazide and methylene linkage, was synthesized starting from alpha-tolunitrile. The BABH and intermediates involved in its synthesis were characterized by spectroscopic methods. Novel poly(amide-hydrazide)s were synthesized by low temperature solution polycondensation of BABH with isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC). Furthermore, two series of copoly(amide-hydrazide)s, based on different mol % of BABH and bis-(4-aminophenyl) ether (ODA) with IPC/TPC were also synthesized. Poly(amidehydrazide)s and copoly(amide-hydrazide)s were characterized by inherent viscosity [eta(inh)], FTIR, solubility, X-ray diffraction (MUD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The polycondensation proceeded smoothy and afforded the polymers with inherent viscosities in the range of 0.18-093 dL/g in (NMP + 4% LiCl) at 30 degrees C +/- 0.1 degrees C. These polymers dissolved in DMAc, NMP or DMSO containing LiCl. The solubility of copolymers was considerably improved in line with less crystalline nature due to random placement of constituent monomers during the copolymerization. XRD data indicated that poly(amide-hydrazide)s from BABH alone and IPC/TPC had higher crystallinity than the corresponding copoly(amide-hydrazide)s derived from a mixture of BABH and bis-(4-aminophenyl) ether (ODA). Polymers showed initial weight loss around 160 degrees C which is attributed to the cyclodehydration leading to the formation of corresponding poly(amide-oxadiazole)s. Copolyamide-hydrazides showed, T(max) between 400 and 540 degrees C which is essentially the decomposition of poly(amide-oxadiazole)s. (C) 2010 Wiley Periodicals, Inc. J App Polym Sci 116: 2441-2450, 2010
Keywords: bis-(4-aminobenzyl) hydrazide; poly(amide-hydrazide); structure-property relations; Thermogravimetric analysis (TGA); x-ray diffractograms